Seafloor morphology and potential gas hydrate distribution in the offshore Niger Delta - B Aminu, Muslim; Samuel B Ojo, (International Journal of Advanced Geosciences, 2024)
Bottom simulating reflectors (BSRs) and seismic pipe features have been used as proxies for defining the distribution of gas hydrate sediments in the offshore Niger Delta. This is the most extensive mapping of gas hydrate sediments in the Delta as of today. The seismic data merge comes from multiple surveys acquired with different parameters and seismic resolutions over the course of decades of oil and gas exploration in the region. Indicated gas hydrate distribution generally follows the structural fabric of the Niger Delta with BSRs occurring along the apexes of the thrust-related ridges that have bathymetric relief on the seafloor. The presence of swarms of seismic pipe features landwards of BSR locations suggests hydrates occur beyond BSR locations. The potential gas hydrates sediment acreage in offshore Niger Delta is 17600 sq-km, representing 20% of the area with a thickness of the gas hydrate stability zone reaching 440 m in the more outboard regions of the Delta. Total gas hydrates sediment coverage likely exceeds this value as BSRs become indistinguishable from sediment strata in regions of flat dips. The presence of double BSRs further suggests the presence of thermogenic gas hydrates in the region and allows to extend the thickness of the potential hydrate zone to 550 m in the outboard regions of the Delta.